Perancangan dan Implementasi Sistem Pengendalian dan Monitoring Penggunaan Peralatan Elektronik Berbasis Internet of Thing (IoT) - Sarmayanta Sembiring; Muhammad Ali Buchari (STMIK Budi Darma, 2021)
A control and monitoring system for the use of IoT-based electronic equipment has been designed with automatic and manual control systems using Arduino Uno, NodeMCU ESP8266, two PIR sensors, three ACS712 current sensors, three Relay modules and two infrared transmitter modules.The automatic control system will turn off the electronic equipment automatically when the two PIR sensors do not detect any movement and the current sensor detects that the equipment is still ON. The sequence of turning off the equipment in this automatic control is to make the equipment in the ON state into standby by sending ON/OFF data through the infrared transmitter module and then cutting off the current to the equipment using the relay module. Especially for lighting equipment, the system directly cuts off the current using a relay module. In manual control, the ON/OFF control of electronic equipment is carried out based on data sent by the NodeMCU ESP8266 to the Arduino Uno whose settings are carried out in the Blynk application on the user's smartphone. The experimental results show that the controller has automatically been able to turn off the equipment in the order that the equipment conditions are ON to standby and standby equipment to be OFF, specifically for lighting equipment in ON conditions to OFF. The manual control system using the Blynk application on the smartphone can already control the equipment by pressing the button on the selected application and the equipment state monitoring system can display equipment state information on the Blynk application according to the data sent by the main controller. The equipment state detection system can detect the state of the equipment ON or OFF with an average error of 4% of 350 times the variation of the test state on equipment consisting of a TV, DVD player and 8W lamp